2003
DOI: 10.1128/aem.69.4.2116-2125.2003
|View full text |Cite
|
Sign up to set email alerts
|

Spatial and Temporal Analysis of the Microbial Community in Slow Sand Filters Used for Treating Horticultural Irrigation Water

Abstract: An experimental slow sand filter (SSF) was constructed to study the spatial and temporal structure of a bacterial community suppressive to an oomycete plant pathogen, Phytophthora cryptogea. Passage of water through the mature sand column resulted in complete removal of zoospores of the plant pathogen. To monitor global changes in the microbial community, bacterial and fungal numbers were estimated on selective media, direct viable counts of fungal spores were made, and the ATP content was measured. PCR amplif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
51
1
2

Year Published

2004
2004
2017
2017

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 75 publications
(57 citation statements)
references
References 62 publications
3
51
1
2
Order By: Relevance
“…Tentative identification suggested that the diatom could be either Gyrosigma or Nitzschia sp. The apparent scarcity of bacteria at this stage may partly be explained by the observation of Calvo-Bado et al (2003) who suggested that most of the microbial communities present within the slow sand filter were tightly attached to the sand grains within biofilms and that lower numbers existed as freeliving bacteria.…”
Section: Resultsmentioning
confidence: 99%
“…Tentative identification suggested that the diatom could be either Gyrosigma or Nitzschia sp. The apparent scarcity of bacteria at this stage may partly be explained by the observation of Calvo-Bado et al (2003) who suggested that most of the microbial communities present within the slow sand filter were tightly attached to the sand grains within biofilms and that lower numbers existed as freeliving bacteria.…”
Section: Resultsmentioning
confidence: 99%
“…Denaturing gradient gel electrophoresis (DGGE) analysis was performed with a DCode mutation detection system (Bio-Rad, Hemel Hempstead, United Kingdom), using 160-by 160-by 1-mm gels of 8% (wt/vol) acrylamide (37:1 acrylamide:bisacrylamide) as described previously (8,40). Linear gradients of between 20% and 70% denaturant for bacterial amplifications and between 30% and 60% denaturant for fungal amplifications were formed by using a gradient maker (BDH, Lutterworth, United Kingdom), with 100% denaturant defined as 7 M urea and 40% (vol/vol) formamide.…”
Section: Methodsmentioning
confidence: 99%
“…PCR amplification of variable regions of the bacterial 16S or fungal 18S rRNA gene was performed with primers 341 (forward [5Ј-CCTA CGGGAGGCAGCAG-3Ј]) (8) and 534 (reverse [5Ј-ATTACCGCGGCTGCT G-3Ј]) (8) for bacterial amplifications and EF4 (forward [5Ј-GGAAGGGRTG TATTTATTAG-3Ј]) (55) and Fung (reverse [5Ј-ATTCCCCGTTACCCGTTG-3Ј]) (36) in a novel combination for fungal amplifications. Both forward primers were modified to include a 40-base 3Ј GC clamp (5Ј-CGCCCGCCGCGCGCG GCGGGCGGGGCGGGGGCACGGGGGG-3Ј) (40).…”
Section: Methodsmentioning
confidence: 99%
“…Biofilters afford many considerable advantages, including simple design and operation, low capital and operating costs, and a low requirement for energy and maintenance inputs [7]. During the past two decades, use of biofilter systems has developed rapidly, and biofilters have been widely used to remove various pollutants originating from aquatic environments [1,[8][9][10][11][12].…”
mentioning
confidence: 99%